Implementation of Student Programs in The Context of Deep Learning in Building Positive Character at SMP Negeri Satu Atap Rimbakarya - Salinan Salinan; Noviyanti Noviyanti; Dinny Mardiana; Suharyanto H Soro (Global Education Journal, 2025)
Education in the era of transformation focuses not only on academic achievement, but also on building individuals who are moral, independent, and ready to face the challenges of the 21st century. Student programs have a strategic role in this situation because they are a place to build values and character through various activities outside of formal learning. Student programs are still faced with several challenges in many schools, among them undisciplined students and poor collaboration. In order for the formation of student character to be more significant and sustainable, the student program management model must be integrated with a deep learning approach. In the context of in-depth education at SMP Negeri Satu Atap Rimbakarya, this study aims to explain and analyze the implementation of student programs to build positive character. The method used is qualitative and uses descriptive analysis. Data was collected through observation, in-depth interviews, and documentation studies, then analyzed using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawn. The validity of the data is carried out by conducting a test of the validity of triangulation of techniques and sources. The results of the study show that the implementation of student programs is carried out systematically through four management functions: structured planning based on the Pancasila Student Profile, collaborative organization, implementation of project-based activities and reflection, and continuous evaluation at the pre, process, and post-stage stages. In conclusion, the student program at SMP Negeri Satu Atap Rimbakarya effectively integrates the management function and philosophy of deep learning in shaping students' positive character holistically and continuously.